Biological Effect Evaluation of Glutathione-Responsive Cyclodextrin-Based Nanosponges: 2D and 3D Studies - Argenziano, Monica (Molecules, 2020)
This study aims to evaluate the bioeffects of glutathione-responsive β-cyclodextrin-based nanosponges (GSH-NSs) on two- (2D) and three-dimensional (3D) cell cultures. The bioeffects of two types of GSH-NS formulations, with low (GSH-NS B) and high (GSH-NS D) disulfide-bond content, were evaluated on 2D colorectal (HCT116 and HT-29) and prostatic (DU-145 and PC3) cancer cell cultures. In particular, the cellular uptake of GSH-NS was evaluated, as their effects on cell growth, mitochondrial activity, membrane integrity, cell cycle distribution, mRNA expression, and reactive oxygen species production. The effect of GSH-NSs on cell growth was also evaluated on multicellular spheroids (MCS) and a comparison of the GSH-NS cell growth inhibitory activity, in terms of inhibition concentration (IC)(50) values, was performed between 2D and 3D cell cultures. A significant decrease in 2D cell growth was observed at high GSH-NS concentrations, with the formulation with a low disulfide-bond content, GSH-NS B, being more cytotoxic than the formulation with a high disulfide-bond content, GSH-NS D. The cell growth decrease induced by GSH-NS was owing to G(1) cell cycle arrest. Moreover, a significant down-regulation of mRNA expression of the cyclin genes CDK1, CDK2, and CDK4 and up-regulation of mRNA expression of the cyclin inhibitor genes CDKN1A and CDKN2A were observed. On the other hand, a significant decrease in MCS growth was also observed at high GSH-NS concentrations, but not influenced by the nanosponge disulfide-bond content, with the MCS IC(50) values being significantly higher than those obtained on 2D cell cultures. GSH-NSs are suitable nanocarries as they provoke limited cellular effects, as cell cycle arrest only occurred at concentrations significantly higher than those used for drug delivery.